The analysis of sustainable development strategies for industrial tourism based on IOA-NRM approach. (20th December 2019) - Lin, Chia-Li
Abstract: Taiwan's economic development has gradually shifted from the manufacturing industry to the service industry. The manufacturing industry faces cheap competition from neighboring countries (such as China and Southeast Asian countries). As industrial enterprises relocate their production facilities to China and Southeast Asian nations, they must think about how to restructure the industry. Industrial tourism has been adopted as a form of industrial transformation. In recent years, an increasing number of conventional industrial enterprises have begun to transform production-oriented manufacturing and production plants into tourism facilities. This trend not only promotes industrial transformation but also helps industrial operators rethink how to create corporate value through service innovation as well as to determine future development directions for the manufacturing industry. Thus, this study attempts to identify the driving force of service facilities based on industrial tourism views. This study can help industrial operators review their value-driving forces while also helping them to understand the critical success factors for industrial transformation and determine the appropriate tourism transformation strategy. Additionally, this study explores tourists' need for industrial tourism and integrates the tourists' preference for service innovation and service demands for industrial tourism. This study proposes the IOA-NRM (innovation opportunity analysis-Network Relation Map) approach, which combines the IOA technique and NRM technique. The service/function of EH (educational heritage) not only increases the product/service knowledge for customers but also strengthens their enterprise identification with educational heritage consciousness. Therefore, the service providers of industrial tourism can identify the service innovation strategies and conventional industrial enterprises to find new market value via the IOA-NRM approach.